Mixed land use and equity in water governance in peri-urban Bangkok - Sajor, E.; Ongsakul, R. (Wiley, 2007)
This article addresses a dearth in the literature on environmental equity in water governance in the desakota, the extended metropolitan region of the great cities of Southeast Asia. Through a case study, the authors describe how, in an intensive mixed land use situation, the actions of new urban users of irrigation canals have degraded the water, unfairly prejudicing low‐income farmers' entitlement to irrigation water of appropriate quality and harming their livelihood. It is argued that certain characteristics of existing land‐ and water‐sector‐related management institutions in Thailand encourage a disproportionate shift of the environmental burden to small farmers. This phenomenon also involves the violation of procedural equity — the farmers' right to be informed, to be able to assert a right to and negotiate for appropriate water, and to participate meaningfully in strategic decisions related to water governance in the peri‐urban area. The problem is mediated by administrative separatism, ambiguity and multiplicity in the functional jurisdiction of water‐related government bodies, and the general lack of a participatory culture in the bureaucracy. The authors further argue that, without state acknowledgement of this form of injustice, establishing appropriate mechanisms and public institutions that will purposively address concerns of environmental equity is a remote possibility, and that this inequity will likely continue to be patterned and inscribed in the peri‐urban geography of the mega‐cities of Southeast Asia.Cet article comble une lacune dans les travaux sur l'équité environnementale de la gouvernance de l'eau dans un desakota, prolongement de région métropolitaine propre aux grandes villes d'Asie du Sud‐Est. Au travers d'une étude de cas, les auteurs décrivent comment, dans une situation d'occupation mixte intensive d'un territoire, les nouveaux usagers urbains des canaux d'irrigation ont provoqué une dégradation de l'eau, faisant injustement tort au droit des agriculteurs pauvres à une eau d'irrigation de bonne qualité et nuisant ainsi à leur source de revenu. En Thaïlande, certains traits des institutions existantes de gestion du sol et de l'eau encouragent un transfert disproportionné de la responsabilité de l'environnement vers les petits agriculteurs. Ce phénomène implique aussi la violation de l'équité procédurale: droit des agriculteurs àêtre informés, à pouvoir revendiquer et négocier une eau convenable, à participer véritablement aux décisions stratégiques relatives à la gouvernance de l'eau dans la zone périurbaine. Le séparatisme des administrations, l'ambiguïté et la multiplicité des compétences fonctionnelles des organismes gouvernementaux liés à l'eau, ainsi que l'absence totale de culture participative dans la bureaucratie sont à l'origine du problème. L'article conclut que, si l'État ne reconnaît pas cette forme d'injustice, la possibilité d'instaurer des mécanismes appropriés et des institutions publiques pour traiter résolument les questions d'équité environnementale est improbable, et que cette inéquité va sans doute continuer à s'inscrire dans la géographie périurbaine des mégapoles d'Asie du Sud‐Est.